The Playskool guide for expectant fathers : the best information, action plans and expert advice for your new adventures in daddyhood - Lipps, Brian (Naperville, Ill. : Sourcebooks, 2007)
These essential guides give parents practical information they need to guide them from pregancy through baby's toddler years.
Includes bibliographical references (pages 263-266) and index.
Keywords: Pregnancy -- Popular works; Fathers; Fathers; Pregnancy; Popular works; Popular works